+0  
 
0
327
4
avatar

Rearrange the formula y = 3x-2/x+1 to make x the subject.

I found this in a test paper, and am struggling to finish it. I have gotten to yx+y=3x-2 but don't know where to go from there. 

Guest Jan 16, 2016

Best Answer 

 #1
avatar
+10

Solve for x:
y = 3 x+1-2/x

y = 3 x+1-2/x is equivalent to 3 x+1-2/x = y:
3 x+1-2/x = y

Bring 3 x+1-2/x together using the common denominator x:
(3 x^2+x-2)/x = y

Multiply both sides by x:
3 x^2+x-2 = x y

Subtract x y from both sides:
-2+x+3 x^2-x y = 0

Collect in terms of x:
-2+3 x^2+x (1-y) = 0

Divide both sides by 3:
-2/3+x^2+1/3 x (1-y) = 0

Add 2/3 to both sides:
x^2+1/3 x (1-y) = 2/3

Add 1/36 (1-y)^2 to both sides:
x^2+1/3 x (1-y)+1/36 (1-y)^2 = 2/3+1/36 (1-y)^2

Write the left hand side as a square:
(x+(1-y)/6)^2 = 2/3+1/36 (1-y)^2

Take the square root of both sides:
x+(1-y)/6 = sqrt(2/3+1/36 (1-y)^2) or x+(1-y)/6 = -sqrt(2/3+1/36 (1-y)^2)

Subtract (1-y)/6 from both sides:
x = sqrt(2/3+1/36 (1-y)^2)+(y-1)/6 or x+(1-y)/6 = -sqrt(2/3+1/36 (1-y)^2)

Subtract (1-y)/6 from both sides:
Answer: | x = sqrt(2/3+1/36 (1-y)^2)+(y-1)/6       or x = (y-1)/6-sqrt(2/3+1/36 (1-y)^2)

Guest Jan 16, 2016
Sort: 

4+0 Answers

 #1
avatar
+10
Best Answer

Solve for x:
y = 3 x+1-2/x

y = 3 x+1-2/x is equivalent to 3 x+1-2/x = y:
3 x+1-2/x = y

Bring 3 x+1-2/x together using the common denominator x:
(3 x^2+x-2)/x = y

Multiply both sides by x:
3 x^2+x-2 = x y

Subtract x y from both sides:
-2+x+3 x^2-x y = 0

Collect in terms of x:
-2+3 x^2+x (1-y) = 0

Divide both sides by 3:
-2/3+x^2+1/3 x (1-y) = 0

Add 2/3 to both sides:
x^2+1/3 x (1-y) = 2/3

Add 1/36 (1-y)^2 to both sides:
x^2+1/3 x (1-y)+1/36 (1-y)^2 = 2/3+1/36 (1-y)^2

Write the left hand side as a square:
(x+(1-y)/6)^2 = 2/3+1/36 (1-y)^2

Take the square root of both sides:
x+(1-y)/6 = sqrt(2/3+1/36 (1-y)^2) or x+(1-y)/6 = -sqrt(2/3+1/36 (1-y)^2)

Subtract (1-y)/6 from both sides:
x = sqrt(2/3+1/36 (1-y)^2)+(y-1)/6 or x+(1-y)/6 = -sqrt(2/3+1/36 (1-y)^2)

Subtract (1-y)/6 from both sides:
Answer: | x = sqrt(2/3+1/36 (1-y)^2)+(y-1)/6       or x = (y-1)/6-sqrt(2/3+1/36 (1-y)^2)

Guest Jan 16, 2016
 #2
avatar
+5

....the question wasn't to solve it, it was to rearrange it to make x the subject

Guest Jan 16, 2016
 #3
avatar
+5

IT IS NOT SOLVING IT!. IT IS FINDING "x" IN TERMS OF "y".  YOU SEE "y" IN THE ANSWER?

Guest Jan 16, 2016
 #4
avatar+78719 
+5

Good work,  guest #1   ......!!!!

 

The key to this problem is to see that (1/3)(1-y)   is actually treated as a coefficient on "x" and then completing the square based on that coefficient

 

 

cool cool cool

CPhill  Jan 16, 2016

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details